Socioeconomic Inequality in Healthcare Utilization in India: Is Health Insurance a Way Out? - Mahapatro, Sandhya R (Journal of Population and Social Studies [JPSS], 2019)
Both the rapidly changing demographics and the epidemiological profile pose major challenges to the health care system in India especially regarding the equitable provision of health care services. Over the past decade, the government has emphasized universal access to healthcare, however, access to healthcare is still inequitable. Studies so far have addressed health inequalities through health outcomes with limited emphasis in quantifying the contribution of the determinants and the role of insurance in tackling such inequalities. Using data from the National Sample Survey (2014-15), this study sought to measure the impact of socioeconomic factors on inequality in healthcare and whether financial protection had any bearing on those conditions. Inequalities were measured through the Concentration Index (CI) and the impact of socioeconomic factors was assessed by the decomposition method. The results suggest that utilisation of inpatient care was based on economic factors and favors the affluent. Impact of health insurance on healthcare utilization, as positive as that might be in principle, was not effective in tackling the economic inequalities. Assessing the performance of the health system by prioritizing the required adjustments, and doing so with an emphasis on ensuring the equity of financial protection measures is important for universal healthcare access.